Exploring senior motorcyclist injury severity crashes: Random parameter model with heterogeneity in mean and variance - Hamsa Zubaidi; Reuben Tamakloe; Nabeel Saleem Saad Al-Bdairi; Ali Alnedawi; Ihsan Obaid (IATSS Research, 2023)
The fatality rates of motorcyclists are substantially higher than for passenger car occupants per registered vehicle and vehicle miles traveled. There is limited information regarding the contributing factors associated with motorcycle injury severity among senior riders (≥65 years). Therefore, random parameter logit models with heterogeneity in mean and variance were developed based on seven years (2012–2018) crashes database at two different locations, intersection and non-intersection roadways in Florida. About 30 indicator variables were significant for both intersection and non-intersection crashes and were categorized under the driver, temporal, spatial, roadway, and other characteristics, driver action, and crash type. Several factors were found to impact the fatal injuries at the intersection directly, and no intersection crashes. However, speeding, dark, and morning crashes are shared by both locations. This paper highlights the importance of considering a specific crash location during the analysis to minimize any possible erroneous and unreliable countermeasures. Various countermeasures were proposed to assist the safety authorities and policymakers to mitigate the senior motorcyclist injury severities related to crashes.